De-radicalization of children and youth by enhancing nationalism and spirituality through national children's learning program - Diaz Syafrie Abdillah; Akbar Reza Muhammad; Athiyatul Ulya; Hafizh Auliyan Sodali; Dian Dakwatul Choiriya; Handayani Handayani; Hafid Algristian (Future Science, 2018)
The teenagers and children are groups that are vulnerable to radicalism. This de-radicalized program is an innovation in the field of community service called